Speckle tracking evaluation of right ventricular functions in children with sickle cell disease - Osama Abd Rab Elrasol Tolba; Mohamed Ramadan El-Shanshory; Mohamed Abd Elaziz El-Gamasy; Walid Ahmed El-Shehaby (Wolters Kluwer Medknow Publications, 2017)
Background: Cardiac dysfunction is a risk factor for death in patients with sickle cell disease (SCD). Aim of the Work: Aim of the work is to evaluate the right ventricular systolic and diastolic functions by tissue Doppler and speckling tracking imaging in children with SCD. Subjects and Methods: Thirty children with SCD and thirty controls were subjected to clinical, laboratory evaluations, and echocardiographic study using GE Vivid 7 (GE Medical System, Horten, Norway with a 3.5-MHz multifrequency transducer) including; Two-dimensional and tissue Doppler echocardiographic study (lateral tricuspid valve annulus peak E' velocity, lateral tricuspid valve annulus peak A' velocity, E'/A' ratio, isovolumetric relaxation time, lateral tricuspid valve annulus S' and septal S' waves and peak longitudinal systolic strain [PLSS] and time to PLSS) were done in six right ventricular segments. Results: There was a significant decrease in right ventricular systolic and diastolic function in patients group when compared to controls. Conclusions: Children with SCD have impaired right ventricular systolic and diastolic functions when compared to healthy children with early evaluation of the systolic dysfunction by speckle tracking imaging technique.